Importance of maternal education on antenatal care visits in Bangladesh (Bangladesh Journal of Scientific Research, 2018)
An attempt has been made to examine whether maternal education influences the antenatal care (ANC) visit in Bangladesh using sequential logistic regression models with an interaction between maternal education and place of residence. For the purpose of analysis, Bangladesh Demographic and Health Survey (BDHS), 2014 data set have been used. The findings emerged from the study show a significant increase of adequate ANC visits among pregnant women with the increase in maternal education level. Moreover, interaction between maternal education and place of residence provides a significant effect on complete ANC visits. The finding justifies an influential impact of maternal education on ANC visits over place of residence. Female participation in the education programs needs to be increased because maternal education signifies a strong positive association with ANC visits.Bangladesh J. Sci. Res. 30(1&2): 23-33, December-2017